Linux operating system : a complete Linux guide for beginners. (Packt Publishing, 2023)
Linux is the number one operating system in the corporate world. The industry's most powerful computers are Linux-based. Linux is a popular open-source operating system that's easy to use and highly secure. Linux offers low-cost servers that can run almost every major web development language available. With the availability of cloud computing, the Linux market share is skyrocketing. If you want to start your career in Linux and have little or no knowledge of Linux, then this course will definitely help. In this course, we will start with the history of Linux distributions, and then learn how to download, install, and configure Linux on your systems. Next, we will get introduced to the file system and terminal where you will learn different Linux directory commands. Later, you will learn how to work with files and directories, how to copy, edit, move, search for a file, and more. Then we will cover system commands such as date, calendar, and sleep, and Utility commands like how to clear, exit or shutdown. After this, we will move to networking where you will learn how to check the IP address and set up a bridged network in VirtualBox. Next, we will cover process and memory. In the last section, you will learn how to create your own Apache server and host a real-time website. By the end of this course, you will gain Linux system administration skills and become an independent user of the Linux operating system. What You Will Learn Get introduced to Linux distributions and understand its history Learn how to set up the Linux environment Explore the Linux file system and terminal Learn how to work with files and directories Learn different system and utility commands Learn how to set up Apache server and host a website on Linux server Audience Anyone interested in learning more about Linux or beginning IT professionals who wish to increase their knowledge of Linux should take this course. This course will also be helpful for those who are considering a career as a Linux system administrator or engineer and need to brush up on the fundamentals. About The Author Ankush Choudhary: Ankush Choudhary is a cloud engineer by profession. He has a degree in information technology and loves working with new tech and computers. His focus and interests include various topics in the fields of computers and technology. Teaching has been a passion for a number of years. In addition to teaching, Ankush has experience as a cloud engineer. His role in this field has provided him with experience and insight into the architecture, deployment, development, and administration of cloud environments. The author also has a newer interest in the area of virtualization and AWS. The author looks forward to the experience and challenge of teaching and learning online with the students. Computer science is a field that covers a vast amount of information and due to its abundance and necessity, it is easily applied to our own lives and the lives of those around us. Hope that your learning journey together makes us enjoy the world of technology!.